2022
DOI: 10.1142/s0218348x22501857
|View full text |Cite
|
Sign up to set email alerts
|

Pull-in Stability of a Fractal Mems System and Its Pull-in Plateau

Abstract: The pull-in instability is the inherent property of a micro-electromechanical system (MEMS) when the voltage is larger than its threshold value. Recently, a fractal MEMS system was proposed to overcome the pull-in instability with great success, and it has opened a total new path for the so-called pull-in stability. This paper suggests a pull-in plateau, a novel concept for qualifying the pull-in stability. The plateau’s basic properties are elucidated, and the effect of the fractal dimensions on the plateau w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Professor Ji-Huan He and his students proposed a novel concept for qualifying the pull-in stability, which is called as He's pull-in plateau. 23 Also, the pull-down instability of a quadratic nonlinear oscillator was suggested by He and coworkers. 7 Applying the ideas directly from Refs.…”
Section: Pull-down Plateaumentioning
confidence: 92%
See 2 more Smart Citations
“…Professor Ji-Huan He and his students proposed a novel concept for qualifying the pull-in stability, which is called as He's pull-in plateau. 23 Also, the pull-down instability of a quadratic nonlinear oscillator was suggested by He and coworkers. 7 Applying the ideas directly from Refs.…”
Section: Pull-down Plateaumentioning
confidence: 92%
“…7 Applying the ideas directly from Refs. [7] and [23] we study He's pull-down plateau of the Toda-like fractalfractional oscillator to illustrate the roes' agglomeration. Firstly, the previous work on He's pull-in plateau of the fractal MEMS oscillator was presented in Ref.…”
Section: Pull-down Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…There are various methods in the literature to deal with the pull-in instability: Anjum et al 10 gave a systematical review on various analytical methods for MEMS systems, Anjum et al 11 showed that the variational iteration method is an efficient tool to the analysis of the periodicity of an N/MEMS, Ji-Huan He et al established a variational theory for MEMS systems, 12 Anjum et al applied Li-He's modification of the homotopy perturbation method with great success, 13 Rehman et al suggested a modified variational iteration method coupled with Laplace transform, 14 and Ji-Huan He et al discovered the pull-in plateau. 15 Carbon-based nanomaterials, including one-dimensional carbon nanotubes (CNTs) and two-dimensional graphene, 16,17 are more attractive in various N/MEMS applications (such as electronic components, mass/gas sensors, and supercapacitors) due to their unique mechanical, electrical, optical, and chemical properties and have become the first choice for sensing applications in MEMS (microelectromechanical systems) and NEMS (nanoelectromechanical systems) devices. [18][19][20][21][22] Graphene is widely used in mass and gas sensing applications because of its low mass and high surface to volume ratio and its good mechanical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods in the literature to deal with the pull-in instability: Anjum et al 10 gave a systematical review on various analytical methods for MEMS systems, Anjum et al 11 showed that the variational iteration method is an efficient tool to the analysis of the periodicity of an N/MEMS, Ji-Huan He et al established a variational theory for MEMS systems, 12 Anjum et al applied Li-He’s modification of the homotopy perturbation method with great success, 13 Rehman et al suggested a modified variational iteration method coupled with Laplace transform, 14 and Ji-Huan He et al discovered the pull-in plateau. 15…”
Section: Introductionmentioning
confidence: 99%